An Assessment on The Role of Cryptocurrency in Modern Kidnapping for Ransom Cases in Cities of Pasay and Paranaque - Desamito Jr.,, Marceliano A.; Bautista III, Leonardol O.; Dela Cruz, Loreta R.; Garcia, Moises B.; Tomas Jr, Cecilio G.; Villa, Elizabeth Buena; Mobo, Froilan D.; Golla, Nathaniel S. (Future Science / FSH-PH Publications, 2025)
The study aimed to address the influence of cryptocurrency on contemporary kidnapping for ransom in the cities of Pasay and Paraňaque as assessed by anti-kidnapping group personnel towards the development of a strategic proposal to combat kid-napping in the digital landscape.This research employed a quantitative-descriptive methodol-ogy, utilizing stratified random sampling as the research design to carefully select respondents from the PNP office Anti-Kidnapping Group. A total of twenty (20) survey questionnaires will be distributed to gather data on the evaluation of PNP per-sonnel regarding the role of cryptocurrencies in contemporary kidnapping for ransom, particularly in relation to investigation, negotiation, and operations. The study's findings indicate that: The Philippine National Police Anti-Kidnapping Group (AKG) should improve educational programs and strategies to address kidnapping for ransom. Mandatory training on proposed initia-tives will be necessary for the PNP AKG. Additionally, the PNP AKG will oversee security in Pasay and Paranaque, and the BSP is actively monitoring developments in virtual currency, particular-ly regarding their potential use in money laundering and other illicit activities, and will take appropriate action as needed. The findings emphasized that strong regulation, including the Anti-Fraudulent Activities in Financial Accounts Act (AFASA) and the suggested amendments to the Bank Secrecy Act, are es-sential and long overdue. The BSP and other regulatory authori-ties in the Philippines must actively oversee cryptocurrencies. Furthermore, the PNP AKG and ACG necessitate revised tech-niques to proficiently obstruct blockchain technology from ena-bling cross-border bitcoin transactions.